miRNA profiling in leaf and cork tissues of Quercus suber reveals novel miRNAs and tissue-specific expression patterns - Chaves, Inês; Lin, Yao-Cheng; Pinto-Ricardo, C; de Peer, Yves; Miguel, Célia (TREE GENETICS & GENOMES, 2014)
The differentiation of cork (phellem) cells from the phellogen (cork cambium) is a secondary growth process observed in the cork oak tree conferring a unique ability to produce a thick layer of cork. At present, the molecular regulators of phellem differentiation are unknown. The previously documented involvement of microRNAs (miRNAs) in the regulation of developmental processes, including secondary growth, motivated the search for these regulators in cork oak tissues. We performed deep sequencing of the small RNA fraction obtained from cork oak leaves and differentiating phellem. RNA sequences with lengths of 19-25 nt derived from the two libraries were analysed, leading to the identification of 41 families of conserved miRNAs, of which the most abundant were miR167, miR165/166, miR396 and miR159. Thirty novel miRNA candidates were also unveiled, 11 of which were unique to leaves and 13 to phellem. Northern blot detection of a set of conserved and novel miRNAs confirmed their differential expression profile. Prediction and analysis of putative miRNA target genes provided clues regarding processes taking place in leaf and phellem tissues, but further experimental work will be needed for functional characterization. In conclusion, we here provide a first characterization of the miRNA population in a Fagacea species, and the comparative analysis of miRNA expression in leaf and phellem libraries represents an important step to uncovering specific regulatory networks controlling phellem differentiation.
Keywords: miRNA; phellem; Quercus suber; secondary growth; Small RNA; Tree